PCR primer : a laboratory manual - Dieffenbach, Carl W; Dveksler, Gabriela S (Cold Spring Harbor Laboratory Press, 2003)
National Institute of Allergy and Infectious Diseases, Bethesda, MD. Summarizes the advances in polymerase chair reaction as well as the more well-established methods. Introduces the basics for PCR and sample preparation, provides protocols for RT-PCR, and analyzes differential expression and cloning. Previous edition: c1995. Hardcover, softcover available.
Keywords: polymery; Genetics; genetika, lékařská genetika; Polymers; genetika